MOLECULAR CHARACTERIZATION OF QUALITY PROTEIN MAIZE AND DOWNY MILDEW RESISTANCE LINES BASED ON SIMPLE SEQUENCE REPEATS (SSRs) MARKER - D. Ruswandi; N. Wicaksana; M. B. Pabendon; M. Azrai; M. Rachmadi; A. Ismail; N. Carsono; F. Damayanti; F. Kasim (Zuriat, 2005)
The information on germplasm diversity and genetic relatedness among elite breeding materials is an important element in maize breeding. Molecular characterization and genetic relationship of 11 QPM-DMR lines were analysed using thirty three SSRs markers. Genetic relationship was determined using Jaccard’s similarity coefficient, and dendogram was then constructed based on the unweighted pair-group method with arithmetical averages (UPGMA). Result showed that (i) all SSRs loci were informative for describing the genotypic variation as showed by their PIC, which ranged from 0.19 for umc1304 to 0.93 for phi112; (ii) the eleven maize inbred lines were clustered into one major group A and small groups B and C that corresponds well with the breeding programs adopted at different institutes of release, and (iii) thus, SSRs marker system is a valuable marker for varietals identification and for genetic diversity study of elite breeding materials.